Stranger things have happened : a novel - West, Kasie (Saturday Books, 2026)
"Bestselling author Kasie West's next adult rom-com about a young woman who makes a deal to save her best friend and her fiance's relationship - as long as she and the fiance's alluring twin brother can convince a marriage counselor that they're a real couple. Needing to take a step back from her lifelong dream of running a bustling restaurant in Los Angeles, a young woman must return to her hometown along the East Coast to care for her ailing mother, despite their strained relationship after her father's abandonment of their family. But as she must balance her obligations to the restaurant, caring for her mother and attempting to mend their relationship, she makes a deal to save her best friend and her fiance's relationship - as long as she and the fiance's alluring twin brother can convince a marriage counselor that they're a real couple"-- Provided by publisher.